2002
DOI: 10.1002/lsm.10060
|View full text |Cite
|
Sign up to set email alerts
|

Low level 809‐nm diode laser‐induced in vitro stimulation of the proliferation of human gingival fibroblasts

Abstract: A cellular effect of the soft laser irradiation on HGF is evident. Its duration, however, seems to be limited. These findings might be clinically relevant, indicating that repeated treatments are necessary to achieve a positive laser effect in clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
97
0
27

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(133 citation statements)
references
References 30 publications
9
97
0
27
Order By: Relevance
“…Eduardo et al 12 verificaram uma maior atividade proliferativa de célu-las tronco da polpa dental humana submetidas a irradiação laser (InGaAlP) de 660nm e 20mW em relação ao controle não irradiado nas mesmas condições de nutrição. Enquanto que Kreisler et al 13 investigaram os efeitos da irradiação laser na proliferação de fibroblastos gengivais humanos. As células foram irradiadas com dose de 1.96-7.84J/cm 2 , usando um laser semicondutor de 809nm e 10mW.…”
Section: Métodos Métodos Métodos Métodos Métodosunclassified
See 1 more Smart Citation
“…Eduardo et al 12 verificaram uma maior atividade proliferativa de célu-las tronco da polpa dental humana submetidas a irradiação laser (InGaAlP) de 660nm e 20mW em relação ao controle não irradiado nas mesmas condições de nutrição. Enquanto que Kreisler et al 13 investigaram os efeitos da irradiação laser na proliferação de fibroblastos gengivais humanos. As células foram irradiadas com dose de 1.96-7.84J/cm 2 , usando um laser semicondutor de 809nm e 10mW.…”
Section: Métodos Métodos Métodos Métodos Métodosunclassified
“…Numerosos estudos experimentais in vitro já foram realizados 7,10,12,13,31,26,27,28 concordando com a hipótese de que a laserterapia seja capaz de influenciar os processos metabólicos celulares, ao aumentar a proliferação de várias células, como os fibroblastos, osteoblastos, queratinócitos, células tronco e células oriundas de tumores malignos.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…For example, LEVL increases the rate of wound healing (3), enhances the fertilizing capability of sperm cells (4), and increases the rate of healing bone defects (5). In vitro studies have found that LEVL increases proliferation of cells as fibroblasts (6), keratinocytes (7), and lymphocytes (8) and induces the respiratory burst in neutrophils (9). The mechanism of photobiostimulation by LEVL is still unclear.…”
mentioning
confidence: 99%
“…Providing laser treatment at low energy levels can be useful and beneficial for healing and regeneration, the predominance of literature suggests that LLLT occurs with visible and near-infrared wavelengths from 633 to 904nm [36][37][38]. Diode laser would be better for biostimulation due to less wavelength than the Er:YAG Laser.…”
Section: Discussionmentioning
confidence: 99%